1918 New Orleans Police Code 114-16 (1918). - (:unkn) unknown (My University, 1918)
Art 15: Ship captains are obliged, within 24 hours of their arrival at port, to deposit gunpowder they may have on board in the powder magazine on the right bank of the river. Also prohibited citizens from storing more than one hundred pounds of gunpowder at any time.
Keywords: GUNPOWDER - STORAGE; GUNPOWDER - TRANSPORTATION